Optimization of the Electrical Performance of Metal Oxide Thin-film Transistors by varying Spray Deposition Parameters - De Lima, Guilherme R. [UNESP] (2018)
Metal oxides like zinc oxide (ZnO) are promising materials for the active layer of thin-film transistors (TFTs) used in the drive circuit of next-generation large-area active matrix displays due to their high electronic mobility, high transmittance in the optical visible range and processability. Traditional deposition techniques employ RF sputtering or pulsed-laser deposition (PLD), which are relatively sophisticated techniques. The deposition of very thin (less than 50 nm thick) layers of ZnO using soluble organic precursors have been extensively investigated recently as an alternative to traditional deposition methods. Solution-based deposition processes include simple and affordable techniques like dip-coating, spin-coating, spray-pyrolysis and ink-jet printing. Spray-pyrolysis is particularly interesting due to the high film uniformity, low cost and high device performance. We carried out several experiments analyzing the performance of ZnO based devices using zinc acetate as organic precursor to confirm that spray pyrolysis deposition is a suitable technique for production of high-performance and reproducible TFTs. Moreover, we observed that device performance can significantly vary with little modifications on the deposition parameters, even for the same active layer composition and pyrolysis temperature. Electrical parameters, as the electrical mobility and the on/off ratio, varied several orders of magnitude, whereas the threshold voltage varied up to 20 V for the tested devices. Deposition parameters as the nozzle height during the deposition, nozzle air pressure and deposition time were varied until we obtained devices with optimum electrical performance. Optimized devices presented mobilities in the order of 1 cm2.V-1.s-1, on/off ratio of about 106 and relatively low operation voltages. A statistical analysis of a great number of devices manufactured using the same deposition parameters was also carried out to assure the reproducibility of the deposition technique.